Payment Methods in Acquisitions of Association of Southeast Asian Nations Bidders - Cao, Kien Dinh; Nguyen, Thuy Thu; Dao, Giang Thi Thu (International Journal of Economics and Financial Issues, 2016)
This paper examines the determinants of methods of payment in M&A transactions in ASEAN countries. We take into account the effects of characteristics of bidders, targets and countries on the choice of method of payment. The findings document the importance of bidders’ technology status, targets’ ownership status, relative size of bidders and targets, and especially the corporate governance variables in the countries that involved in those M&A transactions. In addition, crisis periods also distinguish the choices of payment method for domestic and cross-border M&As in ASEAN countries. Keywords: Methods of payment, ASEAN countries, Mergers, Acquisitions JEL Classifications: G32, G34, G38